A whole-year approach showing that ambient light level influences walking and cycling. (January 2019) - Fotios, S; Uttley, J; Fox, S
Many studies have used surveys to investigate the reactions to changes in lighting from people who walk or cycle. An alternative approach is to use objective data, specifically the number of pedestrians and cyclists present under different lighting conditions. Such data have been reported previously using a daylight savings transition approach. This paper presents a different method for analysing the effect of ambient light conditions in which data from the whole year are examined, rather than only the two weeks either side of the biannual daylight savings clock changes. The results confirm that ambient light has a significant impact: For a given time of day, more people walk or cycle when it is daylight than after dark and more people cycle on cycle trails and walk on foot paths after dark when they are lit than when they are unlit. While both methods use an odds ratio approach, which should account for environmental changes other than lighting, the results suggest the daylight savings method of analysis better isolates changes in weather from the effects of ambient light on travel choice than does the whole-year method.